Processed food trade and developing countries: Protection and trade reform - Allan Rae; Timothy Josling (New Zealand Institute of Economic Research (NZIER), 2001)
Exports of processed foods from developing countries have expanded rapidly in recent times, contributing to those countries' development. Recent research has shown that the developing country exporter's `openness' and agricultural resource endowment offered significant explanations of this export growth. But what if `openness' is enhanced? What if processed and other food trade barriers are lowered? What if trade in manufactured goods is further liberalised? Would developing countries continue expanding processed food exports, or would resources be drawn into textiles and manufacturing? An applied general equilibrium model is used to shed light on these questions through trade policy simulations. Impacts of the simulated reforms on the effective rate of protection of processed foods production are also measured. Most developing regions studied had a positive effective protection rate for processed foods in the base year. This effective protection was reduced when agricultural tariffs were cut. When tariff cuts were extended to manufactured goods, effective protection of food processing in most developing regions increased somewhat, but was still less than base-period protection. Simulated reductions in agricultural and all tariffs increased processed foods exports from developing regions and increased their share of such trade globally, but less so when tariffs of all commodities were reduced.
Keywords: 330; processed food; protection; trade reforms; exports; developing regions; Nahrungsmittel; Export; Nahrungsmittelgewerbe; Zoll; Entwicklungsländer